2017
DOI: 10.1007/s10530-017-1605-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an invasive mud crab on brood success of nest-building fish in the Northern Baltic Sea

Abstract: 1Native fauna in species poor communities, such as those of the Baltic Sea, may be particularly 2 vulnerable to the effects of species invasions. However, the interspecific interactions that 3 result in the negative impacts on native species tend to be poorly understood. One 4 contributing factor to this knowledge gap may be that the vulnerability of native species can 5 vary between different life-history stages. For example, the parental care phase is often risky 6 both for the developing offspring and care-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Such size-assortative choice is most probably due to large males being better able to meet the energetic and ecological demands of owning a large nesting resource. These demands are associated with, for instance, covering the resource with more sand, circulating larger volumes of water when aerating eggs in the nest, or defending the nest and eggs against usurpation, parasitic egg fertilisations or would-be egg predators (Kvarnemo, 1995;Lindström & Pampoulie, 2005;Olsson, Kvarnemo, & Svensson, 2009;Lehtonen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such size-assortative choice is most probably due to large males being better able to meet the energetic and ecological demands of owning a large nesting resource. These demands are associated with, for instance, covering the resource with more sand, circulating larger volumes of water when aerating eggs in the nest, or defending the nest and eggs against usurpation, parasitic egg fertilisations or would-be egg predators (Kvarnemo, 1995;Lindström & Pampoulie, 2005;Olsson, Kvarnemo, & Svensson, 2009;Lehtonen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Wong, B. B. M., Lehtonen, T. K., & Lindström, K. (2018). Spatial and temporal patterns of 629 nest distribution influence sexual selection in a marine fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the Finnish Archipelago, the crab not only forages on mussels and snails but also on amphipods and isopods (Forsström et al 2015), which provoked a shift in the invertebrate community (Forsström et al 2015;Jormalainen et al 2016). Recently, it was shown that the crab prefers the shelter of rocky bottoms independent of food availability (Riipinen et al 2017), and also that they are likely to negatively impact nest-building fishes by taking over their occupied nests (Lehtonen et al 2018).…”
Section: Invasive and Native Predator Speciesmentioning
confidence: 99%
“…his mating success (Lindström, 1988). However, bigger is not necessarily better: occupying a large nesting resource is also likely to be associated with costs, such as the need to use more sand for covering the resource, circulation of larger volumes of water when aerating eggs in the larger nest, or defending the nest and eggs against usurpation, parasitic fertilisations and potential egg predators (Kvarnemo, 1995;Lindström & Pampoulie, 2005;Lehtonen, Vesakoski, Yli-Rosti, Saarinen, & Lindström, 2018). Interestingly, males were found to prefer a large nesting resource in the presence of a second, smaller alternative (Wong, Lehtonen, & Lindström, 2008;Lehtonen, Lindström, & Wong, 2013;Flink & Svensson, 2015), whereas some studies presenting sand gobies with a choice of three different sized resources have found a preference for the intermediate option (Kvarnemo, 1995;Japoshvili, Lehtonen, Wong, & Lindström, 2012;Lehtonen, Wong, & Kvarnemo, 2016).…”
Section: Introductionmentioning
confidence: 99%